Women Drudgery Reduction in Hills Success story of Vivek millet Thresher cum Pearler - Singh, Sukhbir; Kharbikar, H. L.; Joshi, Pratibha; Sahoo, D. C.; Bisht, J. K. (Indian Farming, 2015)
Adoption and use of the millet thresher cum pearler technology in acollective way in the village of Uttarkashi and mechanized postharvest operations of millets of the whole village resulted in saving of 71- 72% and 45-47% cost of operation for threshing and dehusking, respectively and reduced lot of drudgery as compared to traditional system.